Optical properties of remotely doped parabolic quantum wells - Tabata, Américo Sheitiro [UNESP]; Oliveira, José Brás Barreto de [UNESP]; Lamas, T. E.; Sergio, C. S.; Quivy, A. A.; Gusev, G. M.; Leite, JR (Elsevier B.V., 2003)
This work is intended to report on optical measurements in a parabolic quantum well with a two dimensional-three dimensional electron gas. Photoluminescence results show broad spectra which are related to emission involving several subbands on conduction band with the fundamental level of the valence band. This assumption is based on the behavior of the PL peak position and the full width at half maximum in the function of the incident power intensity. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: photoluminescence; parabolic quantum wells remotely doped